Kommunikationsprozesse effektiv und geplant leiten: Grundlagen der Moderation für (Germanistik-)Studierende - Jazbec, Saša; Hansmeier, Judith (2021)
Effective planning and implementation of communication processes: Key basics of moderating for students in German studies and other fields. To effectively plan communication processes and conduct conversations, thorough preparation is needed. This preparation includes content knowledge, practical organization, and the language skills that are necessary for these processes. In so doing, we acquire specific knowledge as well as relevant skills. The aim of the present book is not explicitly to train professional moderators, but to enable students to participate more effectively in interpersonal interaction. Students should be able to conduct conversations fluently and competently and to reflect critically on interaction processes. The theories and concepts in this book are applicable to academic and scholarly contexts, but also to vocational and private settings. As a basis, fundamental theoretical aspects of the special type of communication, moderation, are discussed. Building on this, essential moderation tools and techniques are presented, allowing students to practice and reflect on these techniques, which help build moderating skills.Um effektive Kommunikationsprozesse gestalten und erfolgreich Gespräche führen zu können, braucht man eine intensive inhaltliche, organisatorische und (fremd-)sprachliche Vorbereitung, deren Ziel es ist, sich spezifisches Wissen und relevante Fertigkeiten anzueignen. Das Anliegen dieses Werkes ist es explizit nicht, professionelle Moderator*innen auszubilden, sondern Studierende dazu zu befähigen, an zwischenmenschlicher Interaktion effektiver teilnehmen zu können. Sie sollen in der Lage sein, Gespräche reibungslos, zielorientiert und kompetent auszuführen und Interaktionsprozesse kritisch zu reflektieren. Die vorgestellten Theorien und Konzepte sind dabei auf unterschiedliche Kontexte im universitären, wissenschaftlichen, beruflichen, aber auch privaten Kontext anwendbar. Als Grundlage wird auf grundlegende theoretische Aspekte der speziellen Art der Kommunikation, der Moderation, eingegangen. Zusätzlich werden konkrete Tools und Methoden bearbeitet, praktisch ausprobiert und reflektiert, mit denen man die Moderationskompetenz ausbauen kann.
Keywords: moderation; communication; methods; students; conduct conversations; Moderation; Kommunikation; Methoden; Studierende; Gespräche führen